Developing Photo Analyzing and Bubble Processing Program on Python language - Ivanov, Mikhail V; Gavrilev, Stepan A; Tyurina, Julia M; Yusipova, Anna; Boldyrev, Maxim D (Lecture notes in engineering and computer science, 2019)
This article provides information on methods for determining the size of a gas region in liquids and describes a laboratory bench and a program designed to automatically search for bubbles at the photo. This article, also, shows the correlation between the acoustic and photographic methods of bubble size determination. During this study a special program was developed and tested on images from laboratory bench. The Minnaert`s equation was approved by data delivered from acoustic and photographical methods. By the end of the study, the conclusions about program`s quality and it`s future development were reached.